Action in the North Atlantic - Bacon, Lloyd 1890-1955; Lawson, John Howard 1894-1977 (Warner Home Video, 2012)
This World War II salute to Allied forces stars Humphrey Bogart as First Officer Joe Rossi, who matches tactics with U-boats and the Luftwaffe. The tactics are so on-target that this became a Merchant Marine training film